2015
DOI: 10.1108/jmd-05-2013-0063
|View full text |Cite
|
Sign up to set email alerts
|

An outcomes evaluation of a leadership development initiative

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…As Fischer, Dietz andAntonakis (2017, p. 1735) note on research on leadership processes, "such designs make implicit temporal assumptions regarding the immediacy of effects and/or a stable equilibrium among these effects". With regard to leadership development initiatives, Packard and Jones (2015) found that by obtaining supervisory ratings on participants' job performance and participants' own performance rating, it was possible to moderate the problem of providing data from self-perceptions rather than actual behavior. The use of multiple stakeholders' ratings on coachee's behavior is a way to address the self-reporting challenges associated with EC outcome research, too.…”
Section: Key Challenges For Ec Researchmentioning
confidence: 99%
“…As Fischer, Dietz andAntonakis (2017, p. 1735) note on research on leadership processes, "such designs make implicit temporal assumptions regarding the immediacy of effects and/or a stable equilibrium among these effects". With regard to leadership development initiatives, Packard and Jones (2015) found that by obtaining supervisory ratings on participants' job performance and participants' own performance rating, it was possible to moderate the problem of providing data from self-perceptions rather than actual behavior. The use of multiple stakeholders' ratings on coachee's behavior is a way to address the self-reporting challenges associated with EC outcome research, too.…”
Section: Key Challenges For Ec Researchmentioning
confidence: 99%
“…In such a circumstance, the individual is intrinsically motivated to learn. Second, employees may want to take part in a workplace learning program since team leaders may suggest workplace learning programs for their subordinates during the performance appraisal process (Packard and Jones, 2015;Waldman, Bass, and Einstein, 1987). In particular, team leaders tend to exhibit two completely different methodscoaching or directingregarding the recommended learning programs.…”
Section: H1(b)mentioning
confidence: 99%
“…Respective to the effectiveness of teaching leadership development, research was not found specific to servant leadership; however, several studies that determined leadership development programs in general were effective in increasing job performance, self-efficacy, and self-awareness (Black & Earnest, 2009; Packard & Jones, 2015; van Dierendonck, 2011). Collectively, these findings suggest it may be easier to develop servant leadership than diversity intelligence.…”
Section: Diversity Intelligence An Antecedent To the Compassionate Lomentioning
confidence: 99%